Systematic review of cognitive-behavioural therapy for social anxiety disorder in psychosis - Michail, Maria; Birchwood, Max; Tait, Lynda (MDPI, 2017)
Background: Social anxiety is highly prevalent among people with psychosis and linked with significant social disability and poorer prognosis. Although cognitive-behavioural therapy (CBT) has shown to be effective for the treatment of social anxiety in non-psychotic populations, there is a lack of evidence on the clinical effectiveness of CBT for the treatment of social anxiety when this is co-morbid in psychosis. Methods: A systematic review to summarise and critically appraise the literature on the effectiveness of CBT interventions for the treatment of social anxiety in psychosis. Results: Two studies were included in the review assessing the effectiveness of group CBT for social anxiety in schizophrenia, both of poor methodological quality. Preliminary findings suggest that group-based CBT is effective in treating symptoms of social anxiety, depression and associated distress in people with schizophrenia. Conclusion: The evidence-base is not robust enough to provide clear implications for practice about the effectiveness of CBT for the treatment of social anxiety in psychosis. Future research should focus on methodologically rigorous randomised controlled trials with embedded process evaluation to assess the effectiveness of CBT interventions in targeting symptoms of social anxiety in psychosis and identify mechanisms of change.